THE ROLE OF THE SEMARANG CITY LABOR OFFICE IN MEDIATING INDUSTRIAL RELATIONS DISPUTES REGARDING UNILATERAL TERMINATION OF EMPLOYMENT AGAINST VICTIMS OF WORK-RELATED ACCIDENTS - Mafidhotul Khasanah; Ubaidillah Kamal (Law Research Review Quarterly, 2026)
Unilateral termination of employment against workers who are victims of workplace accidents remains a common issue in industrial relations practices in Indonesia. This situation highlights a gap between the legal protections established in various laws and regulations and their implementation in practice. Workers who are victims of workplace accidents are in a vulnerable position because they not only suffer physical and psychological harm but also face the potential loss of their jobs and livelihoods. This study aims to analyze legal provisions regarding the protection of workers who are victims of workplace accidents from unilateral termination, examine the implementation of mediation by the Semarang City Manpower Office in resolving industrial relations disputes, and evaluate the effectiveness of mediation in providing substantive protection and restoration of workers’ rights following the enactment of LawNo. 6 of 2023 on Job Creation. This study employs an empirical legal research method with a qualitative approach. Primary data was obtained through interviews with industrial relations mediators at the Semarang City Labor Office, while secondary data was obtained through a literature review of relevant laws and regulations, books, and scientific journals. The research findings indicate that, normatively, protection for workers who are victims of workplace accidents is regulated under the Labor Law, the Job Creation Law, the occupational social security system, the Return to Work (RTW) Program, and the Law on Persons with Disabilities. However, implementation has not been optimal due to an imbalance in bargaining power between workers and employers, limitations on mediators’ authority, weak labor oversight, and a preference for resolving disputes through compensation rather than restoring employment relationships. Therefore, it is necessary to strengthen the mediation function, optimize the Return to Work (RTW) Program, and improve inter-agency coordination to realize legal protection and substantive justice for workers who are victims of workplace accidents.